Analisis Pengaruh Kecerdasan Emosional dan Kesejahteraan Psikologis terhadap Keterikatan Pekerja pada Perawat Di Rumah Sakit Pusat Pertamina - Rezqi Ananda Basid; Regina Dentamira Supraba (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2024)
The purpose of this study is investigate the effect of emotional intelligence and psychological well-being on employee engagement. The research was conducted on nurses at Pertamina Central Hospital Extension Modular Simprug. The unit of analysis was at individual level with the sample size of 132 nurses nurses who are currently working at Pertamina Central Hospital Extension Modular Simprug. The data analysis techniques are using multiple regression. The findings of this research shows emotional intelligence has positive effect on employee engagement and psychological well-being has positive effect on employee engagement. Therefore, to maintain employee engagement of nurses, Pertamina Central Hospital Extension Modular Simprug must increase nurses’ emotional intelligence and psychological well-being. Hospital should also select nurse who are high emotional intelligence and increase the pschological well-being to have higher level of employee engagement